(untitled) (Tempo e Argumento, 2010)
In this article, the author discusses the boundaries between history and fiction and their resonance in the history teaching. From the theories of historians like White, Schama, Burke and Gay, this work reflects on more radical and more moderate visions in relation to the flexibility of these boundaries. It expands upon issues which are considered fundamental to their understanding as: the style, the contemporary look and re-creation of the history, poetry and history teaching, narrative, time and fiction. As a conclusion, this investigation considers that, although faint, subtle, outlined and / or demarcated, the boundaries between history and fiction do exist. It also agrees with Burke when he states that, in order to visit those borders more safely, historians need to develop their own fictional techniques. Such visits can also motivate the history teacher to discuss contemporary historiography questions with their students, as well as the contents of the teaching and learning in Basic Education.